Handing over the Baton - Rana, Mowadat Hussain; Dogar, Imtiaz Ahmad; Haider, Nighat (Journal of Pakistan Psychiatric Society, 2021)
It was six years ago, that the Journal of Pakistan Psychiatric Society moved from Peshawar to Faisalabad, after finding its roots there. The job at hand on the repotting of JPPS was to strengthen the stem and ensure fruition. The new editorial board took up the challenge. With an unconditional support of the leadership of Pakistan Psychiatric Society, the JPPS has now established itself as a journal with an enviable standing amongst the scientists, researchers, mental health professionals, postgraduate and undergraduate students of psychiatry and psychology. It now has a wider than ever before, readership in Pakistan and abroad. We are taking this opportunity to hand over the baton, to be picked up by Karachi under a new editorial board. We hope and pray that JPPS will become a robust tree in its new soil. We sincerely hope and wish that in the years to come, JPPS will go places and find new vistas and avenues.